The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
+1 vote
84 views

A value of $x$ that satisfies the equation $\log x + \log (x – 7) = \log (x + 11) + \log 2$ is

(A) 1 (B) 2 (C) 7 (D) 11
 

asked in Numerical Ability by Veteran (46.8k points)
retagged by | 84 views

1 Answer

+5 votes
Best answer

$\log m + \log n = \log mn$

So, $\log x + \log (x-7) = \log (x+11) + \log 2$

$\Rightarrow \log x(x-7) = \log 2 (x+11)$

$\Rightarrow x(x-7) = 2 (x+11)$

$\Rightarrow x^2-9x-22=0$

$\Rightarrow (x-11)(x+2)=0$

$\therefore x=11$

$\because x \neq -2$ , log is undefined for negative number.

answered by Veteran (55.3k points)
selected by


Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true

28,946 questions
36,792 answers
91,067 comments
34,689 users